Experimental study on lateral displacement measurement using air-coupled ultrasound transducers - Iwao MATSUYA (The Japan Society of Mechanical Engineers, 2014)
We propose a novel measurement method for directly measuring the lateral displacement of structures by using air-coupled ultrasound transducers. The normally-distributed far field of an ultrasound transducer in a lateral direction is taken advantage of for the purposes of measuring lateral displacement. The measurement system is composed of three flat-type air-coupled ultrasound transducers and a steel wire as a target. The ultrasound transducers are immobilized at a fixed point, whereas the steel wire is separately arranged on the opposite side. When the steel wire is displaced laterally, the lateral displacement is calculated utilizing the intensity ratio of the reflected ultrasound waves. The accuracy of the lateral displacement measurement is experimentally assessed to be within ± 0.5 mm and the feasibility of the measurement system is discussed. The results show that a developed displacement measurement method will be usable in the field of structural health monitoring due to its accuracy and wide measurement range through the use of several ultrasound transducers.